2016
DOI: 10.5630/jans.36.238
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Japanese Patients with Idiopathic Pulmonary Fibrosis who Cope with Dyspnea

Abstract: This study aimed to clarify experiences of Japanese patients with idiopathic pulmonary fibrosis (IPF) who were coping with dyspnea. We conducted semi-structured interviews with a total of 14 subjects who had developed dyspnea (Borg Scale I or higher) on walking. The data obtained were subjected to qualitative and inductive analyses, which led to the extraction of 36 subcategories. These subcategories were divided into 7 categories, each of which represented the following 7 experiences of IPF patients coping wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…There were very few intervention studies on nursing care. However, there were several informative qualitative studies that involved the narratives of patients with IPF who were living at home regarding the experiences of their self‐care and coping (Duck et al ., ; Igai, ; Schoenheit, Becattelli, and Cohen ). These studies revealed the phenomena experienced by patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There were very few intervention studies on nursing care. However, there were several informative qualitative studies that involved the narratives of patients with IPF who were living at home regarding the experiences of their self‐care and coping (Duck et al ., ; Igai, ; Schoenheit, Becattelli, and Cohen ). These studies revealed the phenomena experienced by patients.…”
Section: Introductionmentioning
confidence: 97%
“…A qualitative study of patients with IPF and coping with dyspnea described additional narratives of patients expressing existential suffering, such as questioning the meaning of living with spiritual pain, psychological distress, and symptoms that are associated with the progression of IPF. These symptoms caused physical and additional psychological and emotional burdens, all of which degraded their QOL (Igai, ).…”
Section: Introductionmentioning
confidence: 99%
“…The sensation of dyspnoea is one of the characteristic symptoms of IPF, which impedes the patient's independent living capacity. Moreover, research found that those patients' experiences of coping with dyspnoea brought up questions and concerns about the meaning of their illness experiences (Igai, ). Therefore, researchers began urging that specific goals fall within the realm of palliative care and needed to include a focus on symptom control (Gilbert & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer tended to receive palliative care for the full range of painful situations including spiritual pain when searching for meaning of life and purpose; unfortunately patients with IPF are still suffering from the burden of symptoms and emotions (Igai, ). In the systematic review on nursing to improve the quality of life for IPF patients, much of the research was qualitative and retrospective research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation